2006
DOI: 10.1039/b512277e
|View full text |Cite
|
Sign up to set email alerts
|

Solvation of uranyl–CMPO complexes in dry vs. humid forms of the [BMI][PF6] ionic liquid. A molecular dynamics study

Abstract: The solvation of the [UO(2)(NO(3))(CMPO)](+) and [UO(2)(NO(3))(2)(CMPO)(2)] complexes (CMPO = octyl(phenyl)-N,N-diisobutylmethylcarbamoyl phosphine oxide) is investigated by molecular dynamics in the "dry" and "humid" forms of a room temperature ionic liquid (IL) based on the 1-butyl-3-methylimidazolium (BMI(+)) cation and the hexafluorophosphate (PF(6)(-)) anion. The simulations reveal the importance of the solvent anions in "dry" conditions and of water molecules in the "humid" solvent. For the [UO(2)(NO(3))… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 61 publications
4
29
1
Order By: Relevance
“…Therefore, am aximum of two TBP molecules may complex to uranyl in the RTIL, with the equatorial sphereb eing additionally filled with two or three Tf 2 Ni onsi no rder to obtain at otal coordination number of five atoms around UO 2 2 + .T he fit of the Sample As hows that the extracteds peciesa tl ow acidic concentrations do not contain any nitrateg roups, anda re of the type [UO 2 .H owever,T f 2 N À anions are weaker ligands than water.T his has been evidencede xperimentally, [44] but also by molecular dynamics calculation. Chaumont and Wipff [45] 2 + .T his confirms that at low acid concentrationt he uranium (VI) extraction occurs by ac ation exchange.…”
Section: Exafs Spectroscopysupporting
confidence: 68%
“…Therefore, am aximum of two TBP molecules may complex to uranyl in the RTIL, with the equatorial sphereb eing additionally filled with two or three Tf 2 Ni onsi no rder to obtain at otal coordination number of five atoms around UO 2 2 + .T he fit of the Sample As hows that the extracteds peciesa tl ow acidic concentrations do not contain any nitrateg roups, anda re of the type [UO 2 .H owever,T f 2 N À anions are weaker ligands than water.T his has been evidencede xperimentally, [44] but also by molecular dynamics calculation. Chaumont and Wipff [45] 2 + .T his confirms that at low acid concentrationt he uranium (VI) extraction occurs by ac ation exchange.…”
Section: Exafs Spectroscopysupporting
confidence: 68%
“…Comparing the [UO 2 + complex further binds 1-3 H 2 O molecules, depending on the denticity of the nitrate and CMPO ligands. [68] 2 2 + , NO 3 À and Cl À ions in the same ratio (1:2:6), but prepared differently, display different UV/Vis spectra, likely due to very slow equilibration kinetics in the viscous ionic liquid. [70] It would thus be quite questionable to attempt to reproduce experimental data by a single simulation alone.…”
Section: Scheme 1 Ionic Constituents Bmimentioning
confidence: 99%
“…The EXAFS fitting showed an average equatorial coordination number of about 4.5 oxygen atoms with a dominant species of [UO 2 (NO 3 )(CMPO)] + , but uncertainty for the denticity of CMPO and NO 3 − . In further studies, by directly dissolving the [UO 2 (NO 3 )(CMPO)] + and [UO 2 (NO 3 ) 2 (CMPO) 2 ] complexes in [BMIm][PF 6 ] ionic liquid, the Chaumont group proved that the species obtained was [UO 2 (NO 3 ) mono (CMPO) mono (H 2 O) 3 ] + .…”
Section: Determination Of Actinide Speciation By Xafsmentioning
confidence: 99%
“…Guilbaud and co‐workers proposed a new force field of the uranyl ion in water, and tested it on some uranyl complexes. They also investigated the solvation of CMPO and [UO 2 (NO 3 )(CMPO)] + as well as UO 2 (NO 3 ) 2 (CMPO) 2 in the ionic liquid based on BMIm + and PF 6 − by MD simulations. It has been suggested that humidity was important for the solvation of these species in ionic liquids.…”
Section: Actinide Computational Chemistry Associated With Exafs and Xmentioning
confidence: 99%